Uji Aktivitas Antimikroba Ekstrak Daun Randu (Ceiba pentandra L.) Terhadap Pertumbuhan Pseudomonas aeruginosa dan Candida albicans - Misriani Ani; Kartika Manalu; Rizki Amelia Nasution (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2023)
One of the traditional plants used by the community is the kapok plant (Ceiba pentandra L.) apart from being cultivated, parts of the kapok plant are also used as building materials, stuffing for mattresses and traditional medicine. The purpose of this study was to determine the activity of randu leaf extract on the growth of Pseudomonas aeruginosa and Candida albicans. This study used a completely randomized design (CRD) with 6 treatment groups, namely the positive control group with chloramphenicol and ketoconazole. The negative control group used 10% DMSO, and the extract concentration group was 70%, 80%, 90% and 100%. The steps carried out in this study included the extraction of kapok leaves using 96% ethanol as solvent, phytochemical screening and antimicrobial testing using the Kirby-Bauer Disc Diffusion method. Analysis of research data using SPSS 21. From the results of this study, it was found that randu leaf extract contained alkaloids, saponins and tannins. Antimicrobial testing with the kapok leaf extract group resulted in an average inhibition zone of 7.57 mm, 8.0 mm, 8.7 mm, and 9.87 mm against Pseudomonas aeruginosa and 4.67 mm, 5.07 mm, 5.32 mm, and 5.65 mm against Candida albicans. The results of the One Way ANOVA test show that Ftable < Fcount which proves that the leaf extract of Randu provides antimicrobial activity in inhibiting the growth of Pseudomonas aeruginosa and Candida albicans.